Modeling and calibration for a simple pendulum - Soares Barreiro, Daiana (2023)
This work aims to present a report on the analysis and calibration of uncertainties of the model that describes the movement of a simple pendulum. The results will be presented through different figures generated by numerical methods and tables whose data are the result of simulation.